The Effect of Tactile-Based Signage Design Intervention on the Wayfinding Permormance of Visually Impaired Students Through Navigation Task - Fakhruddin, Rifqi; Sakya, Kharista Astrini (Gorga : Jurnal Seni Rupa, 2024)
Loss of visual function reduces the accessibility of the environment. A person's ability to move around is closely related to their skills in wayfinding, i.e. finding clues and mental mapping. Individuals with visual impairment use non-visual sensory aspects, such as tactile clues, to form a cognitive map of the structure of the environment. Navigating new and complex environments can cause confusion, anxiety and take longer. Environmental interventions through tactile-based media conditioned into signage design are still scarce, therefore this study aims to try to identify the different roles of three design conditions namely; Rised lines (RL), Texture (TX) and Elevated Graphics (EG) on the wayfinding performance of blind individuals through a navigation task. Data collection involved an experiment with the participation of totally blind and low vision individuals in a simulated environment with three design conditions: raised lines, textures and raised graphics. The experimental process used spatial tasks including; navigation tasks. Measurements on the navigation task used questionnaires and duration scores. This experiment used repeated measure procedures on the three tactile design conditions, as well as a randomized sequence of conditions. The data obtained was analyzed through statistics using repeated measure ANOVA test to test the effect and difference of intervention of three tactile sensor-based signage designs. The findings showed that there was no significant difference in the navigation experience, but there was a significant difference in the navigation task duration score. The Rised Lines (RL) condition showed good performance especially in the aspect of duration score. This research has concluded that, tactile-based signage design has a significant role to help blind individuals understand the environment. This signage design is expected to be a medium for blind individuals, especially special education students in practicing Orientation & Mobility skills properly.